The Character Building of Students at School Ibtidaiyah Madinatun Najah Cilimus Kuningan - Sobar, Amin; Aminah, Siti; Mahmudah, Mahmudah (STAI Publisistik Thawalib Jakarta, 2023)
Character education serves as a strong foundation for schools to shape students with good morals. The aim of this study is to describe and explain the implementation of character education at School Ibtidaiyah Madinatunnajah, Cilimus, Kuningan. This research employs a qualitative approach using a case study method. Data collection techniques include interviews, observation, and documentation. Data processing techniques involve data reduction, data presentation, and drawing conclusions. Data validity techniques include source and technique triangulation. The research findings show the development of the following character traits: Religious character – through prayer activities, girls’ leadership programs, and Qur’an recitation (tadarus). Honesty is demonstrated by not cheating. Tolerance – respecting differences. Discipline: obeying rules. Hard work – completing assignments diligently. Creativity – giving and completing creative tasks. Independence – not relying on others. Environmental awareness – showing care for the school environment. Democracy – providing equal opportunities for all. Social care – caring for others. Conclusion: Character education is effectively implemented through religious activities within the school.